2018
DOI: 10.1002/pc.25180
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nanoplatelets in polychloroprene matrix: An insight to dispersion with a special emphasize to electro‐mechanical properties

Abstract: This work is based on the preparation of graphene‐reinforced elastomeric nanocomposites and an investigation on their electro‐mechanical properties with a special emphasize to electromagnetic interference (EMI) shielding. Polychloroprene rubber (CR) and commercial grade graphene‐based nanocomposites (GnPs) were prepared by using melt mixing and dual mixing (solution followed by melt) technique to study an insight into the dispersion and its effect on various properties namely, mechanical, thermal, conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…[42][43][44] Graphene nanoplatelets (GNPs) possess a high surface-area-to-volume ratio, are lightweight, easy to fabricate, and exible. 45,46 Research has demonstrated that the addition of nanoparticles improves interfacial bonding and enhances the mechanical, thermal, and electrical properties of composites. 47,48 To improve the performance of materials, extensive research has been conducted on the use of nanomaterials as reinforcements and llers in polymer composites, including GNPs and inorganic nanoparticles such as ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] Graphene nanoplatelets (GNPs) possess a high surface-area-to-volume ratio, are lightweight, easy to fabricate, and exible. 45,46 Research has demonstrated that the addition of nanoparticles improves interfacial bonding and enhances the mechanical, thermal, and electrical properties of composites. 47,48 To improve the performance of materials, extensive research has been conducted on the use of nanomaterials as reinforcements and llers in polymer composites, including GNPs and inorganic nanoparticles such as ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-based materials were also incorporated in cementitious materials to upgrade the properties of CBM [25][26][27]. Graphene-based nanomaterials (GBN), an example of carbon-based nanomaterials, were first employed in polymeric matrices [28][29][30] to be used in various applications such as energy storage [31], bio-based applications [32] and sensors [33]. Depending on their synthesis method [34], various types of GBN are available such as graphene (GR), graphene oxide (GO) and reduced graphene oxide (rGO).…”
Section: Introductionmentioning
confidence: 99%
“…Graphene nanoplatelets (GNPs) composites have a high surface area to volume ratio, lightweight, easy to fabricate, and flexible [6][7][8]. The small amount of GNPs in neat composite improved its properties due to the enhancement of the interfacial region [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6. (a) Thermal-CVD and (b) Plasma-enhanced CVD processes where reactants transfer (1), thermal or plasma activation (2), from the main gas stream layer the boundary reactants transport through gas diffusion (3), adsorption of reactants (4), bulk diffusion of species (5), surface migration to the growth of the film (6), desorption of by-products(7), transport of byproducts (diffusion) and return to the main gas stream(8), and by-products transportation from the deposition area (9) By-products transportation from the deposition area; Reprinted with permission from[75].…”
mentioning
confidence: 99%